El Salvador’s Adoption of Bitcoin from the Perspective of One Year: The Influence on the State Budget and a Comparison to Poland’s Legislature - Wnęk, Michał (Journal of Public Governance, 2023)
Objectives: With each passing year, cryptocurrencies are becoming more popular and play an increasinglyimportant role in economic trading. This growing importance is related not only to the increased interest in thissubject, but also to the growing theoretical and practical problems. The author’s goal is to portray circumstances and implications of the adoption of cryptocurrency by the Republic of El Salvador – which recently included bitcoin as part of the state budget – as well as discuss possibility of similar precedent in Poland.Research Design & Methods: Cryptocurrencies are still a relatively new invention and, simultaneously, a complicated one. Therefore, reliable sources and references are still scarce, and those which exist are mostly in the Internet space. In the following article, I have used dogmatic-theoretical method of research in subsequent steps; I analyse proper subject literature, journalistic reports, as well as legal regulations.Findings: El Salvador has become the first country in history that had decided to equate the status of a cryptocurrency with its native currency. Recently, it was also followed by the Central African Republic. However, the Republic of El Salvador takes a step forward and includes bitcoin as part of the state budget, thus bindingthe country’s economic condition with the market pricing of cryptocurrency. A one-year’s investment has, sofar, gone negatively for the country, as Bitcoin price has declined sharply throughout the year. When comparingthe situation of El Salvador to the Polish reality, it should be stated that cryptocurrencies may, in the current legalstate, be part of the state budget. However, this applies only to single instances; therefore, such a negligible share can be omitted in further discussion. Certainly, adoption on El Salvador’s scale is not currently possible. Apart from obvious risks, it would require a thorough reform of not only the legal system, but, above all, the economic mentality of the society.Implications/Recommendations: Given the fact that Bitcoin is a cryptocurrency with neither issuer nor centralauthority, such step is to be considered a significant precedent in the history of world’s economy and for cryptocurrencies themselves. Due to the well-known price volatility of the market, the adoption seems to be highly risky, but, if successful, it may bring measurable benefits to country’s economy. However, the true question is – is it justified to base the state’s budget, which is economic foundation of society, on cryptocurrencies? Almost a year after the adoption, bitcoin price is significantly lower and, consequently, El Salvador’s loss is higher. Yet, bitcoin proved to recover many times – even after slumping over 90%. To conclude, it is advisable to observe El Salvador’s economic situation in order to be able to more precisely define the impact of such a decision in the future, both on the country and on the cryptocurrency market itself.Contribution/Value Added: The adoption of cryptocurrencies by El Salvador was broadly discussed not onlyin the cryptocurrency community, but also in the financial and economical ones. Journalists from around the world as well as international institutions such as the International Monetary Fund and the World Bank all became interested in the situation of El Salvador. In this article, I organise information, assessments, and opinions of the international community regarding the Salvadoran precedent. I also indicate whether and at what level cryptocurrencies can be part of the Polish budget under current legal regulations. The Salvadorian case, due to being a precedent, has already become a valuable lesson for the future legal proposals, research, and discussion. Yet, the development of such a situation may be surprising, which is why further observation is advisable.Article classification: theoretical (conceptual) articleJEL classification: K23, E58, F53